2005
DOI: 10.1007/s00408-004-2538-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mast Cells on the Expression of Adhesion Molecules on Circulating and Migrating Leukocytes in Acute Pancreatitis-Associated Lung Injury

Abstract: Pancreatitis-associated lung injury is an early-occurring and severe complication, still associated with substantial mortality. A number of inflammatory cells and their products are involved in the initiation and progress of the condition. In the present study, acute pancreatitis (AP) was induced by the intraductal infusion of 5% sodium taurodeoxycholate in the rat. Pulmonary endothelial barrier dysfunction was measured by plasma exudation of radiolabeled albumin. Expression of PECAM-1, ICAM-1, and L: -selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Mast cells being important sources of cytokines and chemokines, previous studies have shown in several models of inflammation that these cells play a central role in neutrophils recruitment at sites of injury by delivering TNFa and MIP-2 (Biedermann et al, 2000;Malaviya et al, 1996) or KC (Schramm et al, 2002). Likewise, mast cells may also influence the expression of adhesion molecules and thus the recruitment of neutrophil (Zhao et al, 2005). So, our results suggest that mast cells activation is an early event related to the dose of exposure in SM-induced skin injury, defining the intensity of inflammatory response and modulating the neutrophil influx through secretion of specific cytokines.…”
Section: Discussionmentioning
confidence: 80%
“…Mast cells being important sources of cytokines and chemokines, previous studies have shown in several models of inflammation that these cells play a central role in neutrophils recruitment at sites of injury by delivering TNFa and MIP-2 (Biedermann et al, 2000;Malaviya et al, 1996) or KC (Schramm et al, 2002). Likewise, mast cells may also influence the expression of adhesion molecules and thus the recruitment of neutrophil (Zhao et al, 2005). So, our results suggest that mast cells activation is an early event related to the dose of exposure in SM-induced skin injury, defining the intensity of inflammatory response and modulating the neutrophil influx through secretion of specific cytokines.…”
Section: Discussionmentioning
confidence: 80%
“…It is well known that neutrophil sequestration is implicated in IIR-mediated ALI [34], meanwhile, it has also been reported that treatment with mast cell stabilizer cromolyn sodium can dramatically decrease expressions of ICAM-1 on pulmonary neutrophils in pancreatitisassociated lung injury [20]. Unfortunately, the limitation of the present study did not show the relationships between the mast cell degranulation and neutrophil migration in the development of IIR-mediated ALI.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, Zhao et al have discovered that mast cells are involved in acute pancreatitis-associated lung injury and pretreatment with mast cell stabilizing agents has showed protective effects [20]. Unfortunately, those studies did not specialize the precise function of tryptase during ischemia-reperfusion injury, thus, we speculated that tryptase released from mast cell degranulation would be implicated in acute lung injury during small intestinal ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 95%
“…Expression of CD11b or CD11b/c on leukocytes from blood, lung tissue and bronchoalveolar lavage fluid (BALF) increased after induction of AP (20). It seems that expression of CD11b or CD11b/c on circulating leukocytes correlates with leukocyte infiltration in lung tissue as well as plasma exudation.…”
Section: Are Neutrophils Involved In Pali?mentioning
confidence: 95%
“…Moderate alterations in the expression of L-selectin were noted on both neutrophils and monocytes/macrophages from the circulation and lung tissue. Administration of the mast cell stabilizer downregulated the expression of these adhesion molecules on both neutrophils and monocytes/macrophages (20), indicating that activation of local mast cells plays an important role in leukocyte orientation and activation in the lungs.…”
Section: Are Monocytes/macrophages or Neutrophils Activated?mentioning
confidence: 98%